Preschool language education goals in three Asian countries: A content analysis - Wu, Bo; Jamal Rizal, Razali (www.msocialsciences.com, 2025)
This study addresses the research problem of understanding preschool language education goals across different cultural contexts, focusing on China, Malaysia, and Japan. The objectives are to identify commonalities and differences in their goals and to provide targeted recommendations for improving preschool language education. Using a content analysis approach, the study reveals shared goals among the three countries, including fostering children's language application, diverse expression, and early literacy development. However, significant differences are evident: China emphasizes developing language habits, Malaysia prioritizes the systematic acquisition of language skills, and Japan focuses on nurturing emotional expression. Based on these findings, the study offers tailored recommendations for each country. The conclusions highlight the need for preschool language education to consider national contexts and educational practices more comprehensively and call for further research into the impact of curriculum implementation and coherence on language education outcomes.